Revisão sistemática com metanálise da susceptibilidade genética ao transtorno neurocognitivo associado ao HIV - Caio Squárcio Poças (2017)
Genetic variability is hypothesized to play a role in HIV-associated neurocognitive impairment susceptibility. We have conducted a systematic review followed by a meta-analysis, when possible, to evaluate different genetic polymorphisms associations beyond apolipoprotein E with HIV-associated neurocognitive impairment. Pooled odds ratio (95% confidence intervals) were calculated. Literature search have identified 196 articles. The only polymorphism evaluated in more than three studies was TNF-α-308 (G/A; rs1800629). Included studies (n = 6) were published between 1998 and 2012, and their samples collection were conducted in the USA (n = 3), Netherlands, Australia, Italy, Austria and Germany totaling 1001 HIV infected patients. Quality assessment using Q-Genie tool indicated issues regarding “the non-technical classification of the exposure”, “sample size and power” and “statistical methods and control for confounding”. Pooled odds ratio indicated no association: 0.69 (0.38-1.24) under allelic model, 0.73 (0.35-1.55) under G-allele recessive model and 1.83 (0.33-10.04) under A-allele recessive model. Our meta-analysis provides no support of association between neurocognitive impairment and TNF-α-308 polymorphism and could not access the role of other polymorphisms reported in primary studies. Hence, genetic testing for any of the evaluated genes has no scientific support at this point in the context of neurocognitive impairment and further studies are necessary to identify genetic variants that may be associated with neurocognitive impairment development. Although it is imperative to observe limitations and criticisms raised in this paper regarding primary genetic association studies before conducting additional replications or exploring new association hypothesis.